Islamic Environmental Education for Environmental Sustainability: Analysis Based on Secondary Data From Recent Research - Ridha Aulia; Dawam Suprayogi; Fenti Inayati; Rahmati; Muhammad Rizqiy (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
The global ecological crisis demands an education rooted in moral and spiritual values. Islamic Environmental Education is an interdisciplinary field that combines Islamic theology, environmental ethics, and pedagogy. This study identifies research trends, conceptual gaps, and future directions by integrating bibliometric mapping and a literature review. Using VOSviewer and manual analysis of 103 documents of various types (articles, conference proceedings, and book chapters), this study maps key terms, themes, and developments. The results indicate that Islamic Environmental Education is developing within five main clusters: the implementation of environmental education in Islamic educational institutions; Islam and sustainability; Islamic values and sustainable development; religion and climate change; and Islamic-based environmental character education. Overlay analysis reveals a shift in research focus from conceptual and normative discussions toward practical implementation, environmental governance, and global sustainability. This study also found that the integration of Islamic values into environmental education holds great potential for fostering ecological awareness and sustainable behavior through Islamic schools, pesantren, and eco-pesantren. However, research gaps remain, evidenced by the weak interconnections between certain topics and the scarcity of empirical research on the effectiveness of Islamic Environmental Education programs. This study offers a novel approach by systematically identifying research gaps in the field of Islamic Environmental Education through keyword network visualization, overlay, and density analysis. These findings provide a new direction for the development of an Islamic value-based environmental education model that is more practical, empirical, and measurable.